Hereditary hemochromatosis - Stephen A. Geller; Fernando Peixoto Ferraz de Campos (University of São Paulo, 2015)
Hereditary hemochromatosis (HH) is the most commonly identified autosomal recessive genetic disorder in the white population, characterized by increased intestinal iron absorption and secondary abnormal accumulation in parenchymal organs, not infrequently accompanied by functional impairment. This entity is associated with mutations of the HFE gene (located on the short arm of chromosome 6 at location 6p22.2; closely linked to the HLA-A3 locus), which encodes the HFE protein, a membrane protein thought to regulate iron absorption by affecting the interaction between transferrin receptor and transferrin.